Direct chemiluminescence detection of circulating microRNAs in serum samples using a single-strand specific nuclease-distinguishing nucleic acid hybrid system. Issue 15 (2nd February 2018) - Ling, Kai; Jiang, Hongyan; Huang, Xue; Li, Yang; Lin, Juanjuan; Li, Fu-Rong
Abstract : We developed a microplate-based enhanced chemiluminescence system for the direct detection of circulating miRNAs. The system exhibited a high target sensitivity and specificity, with a detection limit of 3.02 fM. Abstract : We developed a microplate-based enhanced chemiluminescence system for the direct detection of circulating miRNAs. The system exhibited a high target sensitivity and specificity, with a detection limit of 3.02 fM.